Reassessing Cold War Europe - Autio-Sarasmo, Sari; Miklóssy, Katalin (Routledge studies in the history of Russia and Eastern Europe ;, 2011)
Presents a reassessment of Europe in the Cold War period, 1945-91. This book shows that relations between East and West were based not only on confrontation and mutual distrust, but also on collaboration. It reveals that there is in fact considerable interaction and exchange between states, enterprises, associations, organisations and individuals.